The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-35757/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facial Alveolar Bone Thickness and Modifying Factors of Anterior Maxillary Teeth: A Systematic Review and Meta-Analysis of Cone-Beam Computed Tomography Studies

Abstract: Background: Understanding the anatomy of the facial alveolar bone (FAB), provides a prognostic tool for estimating the degree of dimensional ridge alterations after tooth extraction. This study aimed to systematically review the FAB thickness of anterior maxillary teeth measured by CBCT scans. A secondary objective was to assess the facial distance from the cementoenamel junction (CEJ) to the bone crest.Methods: An electronic search was made of Medline, Embase, Web of Science, Cochrane Library and Google Schol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…The width and height of the alveolar process and basal bone at the upper central incisors differ anatomically from the corresponding structures at upper lateral incisors and canines. 24,26,27 Botelho and colleagues 26 described the anatomical features of 174 healthy maxillary central and lateral incisors, and canines. The authors observed that the alveolar process at the central incisor region was significantly wider and longer than at lateral incisors but narrower and shorter than at the canine region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The width and height of the alveolar process and basal bone at the upper central incisors differ anatomically from the corresponding structures at upper lateral incisors and canines. 24,26,27 Botelho and colleagues 26 described the anatomical features of 174 healthy maxillary central and lateral incisors, and canines. The authors observed that the alveolar process at the central incisor region was significantly wider and longer than at lateral incisors but narrower and shorter than at the canine region.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant anatomical difference between premolar and anterior sites, especially regarding the thickness of the buccal bone wall. [22][23][24] A recent systematic review reported that, in premolar sites, the thickness of the buccal wall is greater than 1 mm (1.09-1.96) while at central incisor sites the corresponding value is markedly reduced, about 0.8 mm. 24 Thus, it is plausible to suggest that the healing of a grafted gap would be better protected by the thicker buccal wall at the premolar sites than by the thin buccal wall at the central incisor sites, which would have promoted superior bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being the gold standard in the evaluation of hard tissues, CBCT is incapable of recording soft structures, and there is also difficulty in locating anatomical structures, making correct visualization difficult and may generate little precision for locating these structures in the generated image [1,17].…”
Section: Conical Beam Computerized Tomography (Cbct)mentioning
confidence: 99%
“…In this regard, it is necessary to identify ideal situations for the use of cone beam or fan beam techniques, knowing the specific indication for each one and its applicability, its advantages and disadvantages [14,15,16,17], in addition to a comparison between Cone Beam Computed Tomography and Spiral Computed Tomography in the field of dentistry regarding Oral and Maxillofacial Surgery and Traumatology [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ideal implant axis is proposed to correspond to the axis of the contralateral and adjacent tooth inside the alveolar bone, and the implant is inclined to palatal [8,9]. Limited by insufficient bone dimensions around the tooth root, especially on the labial side, the root apex, and a thin gingiva phenotype, it is hard to place an implant following the axis of the contralateral corresponding tooth, as bone fenestration and dehiscence may occur [10][11][12]. Thus, a pre-implantation evaluation of the root angle, accounting for the characteristics of the surrounding implant-related hard and soft tissues, is crucial for planning an immediate implant placement.…”
Section: Introductionmentioning
confidence: 99%